HUBUNGAN PERAN AYAH DENGAN STATUS GIZI PADA BALITA DI DUSUN VI DESA LAUT DENDANG - Agnes Monnica Sari Lahagu; Hizkianta Sembiring (Jurnal Riset Multidisiplin Edukasi, 2025)
The role of fathers in the family is an important aspect that often receives less attention in research related to child growth and development, especially in the context of the nutritional status of children under 5 years. Nutritional status is an important marker in assessing a person's health condition. The balance between nutrients obtained from food consumption and the body's nutritional needs plays a crucial role from growth to adulthood. The first 1000 days of life have a major impact on a child's future growth and development. Focusing on rich nutritional intake is one of the keys to forming quality human beings, especially in toddlers. Objective: To determine the relationship between the role of fathers and nutritional status in children under 5 years in Laut Dendang Village. Method: Quantitative research method with a descriptive analytical design with a cross-sectional survey. The sampling technique used total sampling. Spearman's correlation test was used to analyze the data in this study. Results: The results of this study indicate that there is a relationship between the role of fathers and nutritional status in children under 5 years in hamlet VI, Laut Dendang Village with a p value = .001 or p < 0.005. Conclusion: There is a significant relationship between the role of fathers and nutritional status in children under 5 years. Recommendation: Future researchers are advised to incorporate the role of fathers into nutritional status to add other variables that may influence nutritional status in children under 5, such as maternal education, family socioeconomic status, and access to health services.